Development of a Project-Based Learning Monitoring Application for Programming Courses - Bonda Sisephaputra; Ghea Sekar Palupi; Ronggo Alit; Reisa Permatasari (Journal of Economics, Business, and Government Challenges, 2023)
In higher education programming courses, students often perform individual practical activities using their own devices, resulting in varying conditions and difficulty in ensuring proper application of the taught concepts. Limited access to equipment further hampers student progress. To address these challenges, implementing the Scrum framework in programming courses is proposed. Scrum offers problem-solving approaches emphasizing collaboration, self-organization, and cross-functional teams for effective teamwork and optimal solutions. However, existing project management tools like Trello and Notion, although free, have limitations when applied to Scrum. Trello lacks multi-sprint support, while Notion's complex customization features complicate usability. To overcome these limitations, this research aims to develop an application specifically tailored to Scrum practices. The objective is to design and create a comprehensive application that serves as both a learning platform and a project management tool. By leveraging this application, students will be able to enhance their learning experience and perform better project management, ensuring effective collaboration and communication among team members. The proposed application will address the limitations of existing tools and provide a seamless Scrum implementation within the programming course. Ultimately, the research seeks to improve the overall effectiveness and efficiency of programming education by empowering students with a robust and user-friendly platform that aligns with the Scrum framework.